The racial equality proposal at the 1919 Paris Peace Conference - Shimazu, N; Shimazu, Naoko (1995)
﻿ This thesis is a study of the racial equality proposal at the Paris Peace Conference. It explores Japanese motivations for submitting the proposal, and the responses of the British and American governments which eventually defeated it. The thesis uses an analytical framework based on five categories of possible explanations for the proposal: immigration, universal principle, great power status, peace conference politics and bargaining, and domestic politics. The thrust of the analysis contained in the thesis is as follows. For Japan, the proposal meant three things: a means of reaffirming its great power status by securing racial equality with the western great powers in the League of Nations; a justification for Prime Minister Hara whose pro- League position was maintained by a fragile domestic consensus against sceptics in the government and the wider public; and a means of resolving Japanese immigration problems in the United States and British Dominions. But for Japan the proposal was not originally intended as a demand for universal racial equality. For Britain, the proposal was unacceptable because it meant "free immigration" of non-white immigrants into the Dominions. In particular, Australia adamantly opposed it also because of its political significance for Australian public opinion. For the United States, Wilson's determination to create the League of Nations at almost any cost led him to impose a unanimity ruling at the crucial vote on llth April 1919. Other explanations worked in the background. The proposal highlighted the importance of the link between race and great power status for Japan, Japan's insecurity concerning the League of Nations and the West, and Japan's different approach to international relations. Moreover, the failure of the proposal revealed the limits of Wilsonian idealism in that neither Britain nor the United States at that time seriously considered the possibility of universal racial equality.